Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Construction of Schiff-base binding site in confined 2D nanochannels for efficient gallium adsorption - Cong Li; Ming Qiu; Chenxi Shi; Fuxin Qiu; Qiongqiong He; Zhuang Li; Wenpeng Li; Jingtao Wang; Guoli Zhou (Desalination, 2026)

Rapid in-situ recovery of starved anammox consortia: Metabolic stimulation and microbial synergy driven by organics and oxygen - Yihao Qiu; Chenrong Gu; Jiaqi Han; Jiaqi Zhang; Qi Zhang; Rong Li; Xiao-Ming Ji (Environmental Research, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Harnessing sunlight-driven peracetic acid for rapid pathogen inactivation in surface waters - Yibo Wang; Ming Zheng; Jialin Li; Xinyu Ma; Shenqi Lu; Zhiyong Chen; Yajie Gao; Jiayi Wang; Wenhui Qiu; Rongrong Xuan (Chemical Engineering Journal, 2026)

Fe–Mn Modified Hydrochar for Competitive Cd and Pb Adsorption in Wastewater - Jibo Long; Yongjie Li; Bingyu Li; Yige Dai; Yimin Zhou; Zhuoqing Li; Cheng Qiu; Qinghai Liu; Ming Lei (Water, Air, & Soil Pollution, 2026)

Soil macrofauna mucus bacterial community: Insights from cultured earthworms and snails - Jia-Jia Gu; Ming-Xin Li; Shuai-Fei Ye; Qiu-Yu Gan; Si-Si Chen; Cheng-Wei Tao; Jing Wen; Xin-Li An; Yu-Ling Jiang; Hong-Tao Wang (Soil Ecology Letters, 2026)

Mechanistic Insights into Mercury Tolerance and Detoxification in the Potential Hyperaccumulator Fern Pteris vittata - Hongye Wan; Xiaoli Qian; Guangle Qiu; Ming Ao; Le Wang; Longchao Liang; Jialiang Han; Md. Habibullah-Al-Mamun; Jinjuan Li; Pan Wu; Shouyang He; Xiaohang Xu (Journal of Hazardous Materials, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Dual-responsive hydrogel coils with shape memory effect for enhanced aneurysm embolization - Min Ye; Ming Qiu; Yunpeng Cai; Nanxiang Li; Jianguo Han; Yan Zhou; Yue Xi; Hongyu Zhao; Yujie Liao; Xinpeng Niu; Long Han; Qingsong Xu; et al. (Chemical Engineering Journal, 2026)

Shrubification increases spatial heterogeneity in soil C:N:P stoichiometry to considerable depth in grazed alpine meadows - Jie Chen; Qiu-jin Ma; Bin Jia; Fen-Can Li; Han Mao; Shu Gang; Yawen Li; Xiao Ming Mou; Xiao Gang Li (CATENA, 2026)

Gut microbial dysbiosis in a Southern Chinese cohort of patients with Parkinson's disease - Yi Ming Li; Qiu Zhi Shao; Chih-Yuan Ko; Yunfei Chen; Donald Robert Haley; Hanadi Y. Hamadi; Mei Zhao (Antonie van Leeuwenhoek, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Acidification associated with plant phosphorus-acquisition strategies decreases nutrient cycling potential of rhizosphere bacteria along the Hailuogou post-glacial chronosequence - Xiao-Long Li; Hongyang Sun; Jun Zhou; Yang Chen; Hong-Qiu Du; Yue-Xin Ming; Shuang Wu; Hans Lambers (Plant and Soil, 2026)
Background and aim Soil nutrient availability, acidification associated with plant phosphorus-mining strategies, and fine root foraging all influence nutrient cycling. However, their relative impacts on microbial nutrient cycling during primary succession remain unclear. Methods We studied a 130-year primary succession along the Hailuogou post-glacial chronosequence in southwest China. Early-successional stages (1–3) are dominated by Hippophae tibetana , which is gradually replaced by Populus purdomii . In the climax community (stage 4), Abies fabri replaces P. purdomii . We collected rhizosphere soil, roots, and leaves from the dominant species, analyzing how phosphorus-acquisition strategies (proxied by soil pH, leaf manganese concentration and fine-root morphology) influenced bacterial nutrient-cycling gene abundance, based on 16S rRNA sequencing. Results Rhizosphere pH and the abundance of genes encoding enzymes involved in ammonium and nitrate assimilation, denitrification and phosphorus mobilization were significantly lower for H. tibetana and A. fabri than for P. purdomii . In contrast, P. purdomii exhibited a significantly higher specific root length. Linear mixed models reveal that leaf manganese concentration was positively correlated with soil acidification. Multiple regression models show that nutrient-cycling potential was more significantly linked to soil pH than to fine-root morphology or soil nutrient availability. Structural equation models indicate that the reduced nutrient-cycling potential was indirectly associated with soil acidification through bacterial co-occurrence networks rather than bacterial richness. Conclusion Soil acidification, associated with phosphorus-mining strategies of H. tibetana and A. fabri , may inhibit microbial nutrient-cycling potential during primary succession. This highlights the interactions between plant nutrient-acquisition strategies and microbial processes in shaping terrestrial nutrient cycling.

Edge Loading and Wear Risk Analysis of a Marine Water-Lubricated Stern Bearing Considering Shaft-Deflection-Induced Journal Tilting - Xianyi Li; Jingjun Lou; Zhimin Chen; Maoting Tan; Ming Yang; Binbin Qiu; Haibo Wan (Journal of Marine Science and Engineering, 2026)
Classical hydrodynamic lubrication studies of journal bearings routinely invoke two simplifying assumptions: the axially rigid–straight journal assumption and the structure–lubrication decoupling assumption. For marine water-lubricated stern bearings, propeller overhung loading induces non-negligible shaft deflection across the bearing length, and the multi-support shafting makes the stern-bearing reaction force impossible to determine from rigid-body statics alone. Both assumptions must be removed within a single analysis framework. This study develops a coupled lubrication–rotor framework that combines a two-dimensional steady Reynolds solver with groove masking, a Winkler elastic liner, and a ROSS-based Timoshenko rotor finite element model through bidirectional reaction-force–tilt feedback. A normalised axial load distribution indicator Iw(z), defined from the axial film-pressure profile, is introduced as a scalar boundary quantity linking the elastohydrodynamic lubrication solution to downstream wear evolution models. Condition decomposition and open-loop tilt sweeps show that the coupled-convergence tilt reduces hmin by 65.7%, raises pmax by 84.5%, and shifts the axial reaction-force distribution and Iw(z) peak toward the stern end. Axial non-uniformity intensifies monotonically with the increase in tilt angle, and beyond a threshold tilt, the HD/EHL solver no longer converges for a hard phenolic liner, establishing the applicability upper bound of the framework.

Expression of Transforming Growth Factor Beta 1 in Lung Adenocarcinoma and Its Relationship with Circulating Tumour Cells - Ning Chen; Duo-Jun Qiu; Jian-Zhu Yang; Gui-Yun Zhu; Li-Fei Kang; Xiao-Ying An; Zhi-Ming Xu; Xiao-Xia Li (Biochemical Genetics, 2026)

Systematic characterization of FBP gene family in Saccharum reveals ScFBP3 as a key regulator of sucrose-mediated plant branching - Huiwen Zhou; Hanmin Luo; Minyi Wei; Ting Luo; Faqian Xiong; Ming Li; Lihang Qiu; Haifeng Yan (Plant Science, 2026)

High-efficiency integration of capacitive deionization and electricity generation in single cycle enabled by basswood-derived free-standing carbon electrode - Yao Qiu; Rui Zhang; Shuyu Kong; Yishuo Teng; Dongling Li; Ming Hou; Jingwen Wang; Yongzhao Hou; Guangwu Wen; Dong Wang (Desalination, 2026)

REE source, fractionation and enrichment behavior in the Tuguanzhai-Maliping ion-adsorption REE deposit, Tengchong Block (SW China) - Zhong Tang; Congfa Bao; Tianxue Ming; Hanjie Wen; Xiaohu He; Hao Cheng; Jiaxin Liu; Zewei Pan; Liang Li; Jiasheng Wang; BeiBei Chen; Kunfeng Qiu (Acta Geochimica, 2026)

Apparent resistivity evaluation method of slurry diffusion-solidification and grouting effect of water-bearing fractured rock mass - Hao Xu; Zhen-zhong Xing; Sheng-quan He; Lian-zhi Yang; Yi Zhu; Da-zhao Song; Yu Zhang; Jin-tao Dang; Qiang Liu; Li-ming Qiu; Ping Wang (Journal of Applied Geophysics, 2026)

Corrigendum to “Modification of starch traits in commercial wheat through TaWaxy gene editing” [Carbohydrate Polymers 368 (2025): 124105] - Yuliang Qiu; Xi Li; Ming Fan; Huali Tang; Shuangxi Zhang; Weihong Huang; Zhiyang Han; Surong Wang; Hao Peng; Yonggui Xiao; Xingguo Ye; Ke Wang (Carbohydrate Polymers, 2026)

Analysis of genetic diversity and population structure in Shaoyang tea plants (Camellia sinensis) utilizing KASP markers and SNP loci - Jin Li; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Jun Tang (Genetic Resources and Crop Evolution, 2026)

Iron plaque crystallinity driven by phosphorus gradients directs Cd/As partitioning in rice - Jibo Long; Qian Zhu; Hongyu Fu; Bingyu Li; Yimin Zhou; Zhuoqing Li; Jiaxiang Wang; Cheng Qiu; Qinghai Liu; Ming Lei (Cereal Research Communications, 2026)

Two new diterpenoid alkaloids from Aconitum legendrei Hand.-Mazz - Ming-Lu Zheng; Feng-Tai Qiu; Qing Tang; Lin Chen; Qin He; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Multidimensional analysis of the microbiota and fermentation quality of High-temperature Daqu from six distilleries in Guizhou Province - Yunxia Yang; Fengshuang Pan; Jianmeng Zhu; Ming Jiang; Chunhui Wei; Xuelian Huang; Xiangyong Zeng; Xia Liao; Wenying Fang; Shuyi Qiu; Dounan Li (Food Bioscience, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Eliminating Microcystis aeruginosa and secondary pollutants via photo-Fenton process over Iron-MOF - Hong- Yu Chu; Zheng-Xing Liu; Jian-Feng Wang; Xuchun Qiu; Fu-Xue Wang; Shao-Long Chen; Hui-Min Yu; Fei Wang; Guang-Chi Liu; Ruo-Xuan Mei; Xin-Jie Li; Xiao-Hang Xu; et al. (Water Research, 2026)

Evidence of heterogeneity in the mantle source of Quaternary Naozhou Island basalts from REEs and Sr-Nd-Pb isotopes - Cui Xiao-Ge; Li Zhi-Hua; Xie Shi-Xiong; Yang Wen-Jian; Wang Ming-Qiu; Cheng Liu-San; Gao Cai-Xia; Jiang Hong-Liang (Lithos, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Plasma MicroRNA and Protein Signature Associated with Obesity in the Chinese Han Population Using MicroRNA Omics and Proteomics Analysis of 1026 Subjects - Yun-Xia Xie; Jian-Ge Qiu; Zhao-Hui Yang; Chen Ding; Le-Ming Shi; Si-Jia Wang; Li Jin; Bing-Hua Jiang (Phenomics, 2026)

Dehydrocostus lactone induces apoptosis and mitophagy in gastric cancer cells through the ROS-mediated mitochondrial pathway - Qiuxiong Chen; Ying Li; Junjie Mu; Qian Ming; Chaohong Zhu; Ziyue He; Mengyue Ma; Xiaoqin Long; Hui Wu; Baoli Qiu; Lihe Zhang; Xian Yang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Application of polyaluminum chloride and anionic polyacrylamide in the solid-liquid separation pretreatment of aquaculture tailwater - Jianping Xu; Yishuai Du; Hexiang Wang; Guogen Su; Jiawei Zhang; Fudi Chen; Ming Sun; Huiqin Tian; Li Zhou; Tianlong Qiu; Jianming Sun (Aquacultural Engineering, 2026)

Baicalin-aluminum complexes inhibit growth and suppress virulence of enterotoxigenic Escherichia coli in vitro - Chun Ye; Xingyue Li; Yunqi Liu; Yuqian Chen; Ming Zhao; Ronghua Yin; Qirong Lu; Jin Liu; Yu Liu; Shulin Fu; Yinsheng Qiu (Toxicon, 2025)

Dynamic response analysis of topside transportation using SPMT - Ming Qiu; Min Zeng; Mingzhi Li; Yibin Lv; Changwei wan; Zhengang Wang; Yanping He (Ocean Engineering, 2025)

Corrigendum to “Identification and in vitro anti-inflammatory activity of different forms of phenolic compounds in Camellia oleifera oil” [Food Chem. 344 (2021) 128660] - Tao Zhang; Fangcheng Qiu; Li Chen; Ruijie Liu; Ming Chang; Xingguo Wang (Food Chemistry, 2025)

Bioactive CS/SS31-SeNPs nanoplatform for dual mitochondrial targeting and ROS scavenging in peri-implantitis therapy - Panpan Ming; Wenqing Zhu; Yuwen Wei; Jingyi Ma; Xinyan Zhu; Xuan Zhou; Shudi Li; Jing Qiu (Chemical Engineering Journal, 2025)

A feasible strategy of photothermal nanocellulose/chitosan porous composite with brine tolerance and magnetic controllability for solar-driven polluted seawater purification - Yu Qiu; Chaoyang Zhang; Ming Zhang; Dingqiang Zheng; Dongsheng Song; Shoufu Long; Zhenghui Li; Zhe Zhang; Zhimin Zhao (Carbohydrate Polymers, 2025)

Study on the mechanism of costunolide inhibiting triple-negative breast cancer by EGFR ubiquitination and degradation to suppress the ERK/AKT signaling pathway - Ying Li; Junjie Mu; Qiuxiong Chen; Qian Ming; Chaohong Zhu; Yujie Xiao; Baoli Qiu; Xue Zhang; Baoshun Zhang; Xian Yang (Journal of Molecular Histology, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Corrigendum to “LSTM-transformer hybrid model predicts and unveils Total phosphorus dynamics and pollutions in Poyang Lake” [Sci. Total Environ. 1003 (2025) 180622] - Yihan Li; Hua Wang; Yanqing Deng; Dongfang Liang; Ming Qiao; Jiayao Dou; Zhiheng Qiu; Linyou Chu (Science of The Total Environment, 2025)

LSTM-Transformer hybrid model predicts and unveils total phosphorus dynamics and pollutions in Poyang Lake - Yihan Li; Hua Wang; Yanqing Deng; Dongfang Liang; Ming Qiao; Jiayao Dou; Zhiheng Qiu; Linyou Chu (Science of The Total Environment, 2025)

Radial oxygen loss of Typha latifolia outperforms microbial effects in heavy metal(loid) stabilization - Taicong Liu; Liying Lan; Yuanyuan Li; Daijie Chen; Ming Ao; Shuting Tang; Haojie Qu; Chao Jin; Miaoyue Zhang; Roland Bol; Jean Louis Morel; Zhihong Xu; et al. (Environmental Research, 2025)

Why not use tertiary amines to prepare anion-exchange membranes for desalination with electrodialysis? - Shuaijun Yu; Yixiang Yu; Yan Zhang; Yangbo Qiu; Tong Mu; Ming Li; Zhipeng Xu; Qiang Wei; Jiangnan Shen (Chemical Engineering Journal, 2025)

Modification of starch traits in commercial wheat through TaWaxy gene editing - Yuliang Qiu; Xi Li; Ming Fan; Huali Tang; Shuangxi Zhang; Weihong Huang; Zhiyang Han; Surong Wang; Hao Peng; Yonggui Xiao; Xingguo Ye; Ke Wang (Carbohydrate Polymers, 2025)

Review on Litopenaeus vannamei recirculating aquaculture technology: basic equipment, influencing factors, emerging technology, and sustainability - Jianping Xu; Tianlong Qiu; Yishuai Du; Li Zhou; Fudi Chen; Ming Sun; Jianming Sun (Aquaculture International, 2025)

Efficacy of a non-recombinant NADC34-like PRRSV-2 vaccine candidate against a recombinant NADC34-like PRRSV-2 isolate - Ming Qiu; Shuai Li; Meng Cui; Shuai Yang; Xiaoyang Zhu; Yifan Meng; Yanhan Lin; Hong Lin; Zhe Sun; Yuan Wang; Sen Jiang; Wanglong Zheng; et al. (Veterinary Microbiology, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Study on mechanism of in-situ hydrogen generation based on molecular dynamics simulation from pyrolysis of heavy oil - Houfeng He; Yuning Gong; Mingguo Peng; Haoran Zheng; Tian Feng; Ming Zhang; Qiu Li; Pengcheng Liu (Fuel, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Characterizing Gray matter atrophy patterns associated with accelerometer-measured sedentary behavior: a population-based study - Minle Tian; Xiaolei Han; Ming Mao; Xiaomeng Li; Yi Dong; Jiahao Ding; Qinghua Zhang; Shi Tang; Xiaojuan Han; Lin Song; Tingting Hou; Lin Cong; et al. (Brain Imaging and Behavior, 2025)
Evidence has linked self-reported sedentary behaviors with dementia and cognitive impairment; however, the underlying mechanisms remain poorly understood. We investigated the associations of accelerometer-measured sedentary behavior patterns with gray matter atrophy patterns in rural-dwelling older adults, while taking into account the manner in which sedentary time is accrued (in short or long bouts). This community-based study involved 911 dementia-free older adults (age ≥ 60 years, 59% women) who participated in both ActiGraph and brain MRI substudies within MIND-China (2018–2020). Sedentary behavior parameters (total sedentary time, mean sedentary bout duration, and sedentary breaks) were recorded with accelerometers. Regional gray matter volumes (GMV) were measured using voxel-based morphometry (VBM) methods. Data were analyzed using the general linear regression models, restricted cubic spline curves, and VBM analysis. There was an inverted U-shaped association between daily sedentary time and GMV in temporal, cingulate, and medial temporal cortex, while longer mean sedentary bout duration was linearly related to decreased GMV in total, frontal, temporal, insula, cingulate, and medial temporal cortex. Greater daily time spent in light or moderate-to-vigorous physical activity (LPA and MVPA) was correlated with larger insula GMV. The VBM analysis suggested that prolonged daily total sedentary time and mean sedentary bout duration were significantly associated with smaller GMV in extensive brain regions, especially in thalamus and insula. In conclusion, gray matter atrophy associated with sedentary behavior in older adults is characterized by reduced GMV in global, frontal, temporal, medial temporal, and cingulate cortex, especially in the insula and thalamus regions.

6,7-Dimethoxy-3H-Quinazolin-4-One as a dual-function inhibitor of polyphenol oxidase and bacteria: biological evaluation, mode of action, and anti-browning studies - Xiu-Zhen Li; Jin-Rui Qiao; Yi-Rui Wu; Dong-Yan Zhou; Yu-Dan Shi; Shu-Meng Zhu; Qiu-Han Bai; Xiao-Lei Xia; Wei-Ming Chai (Food Bioscience, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

The ultrastructure of the Cretaceous feathers highlights the evolution of the feather - Jiajia Wang; Rui Qiu; Qian Chen; Di Liu; Tongbo Zhang; Ying Li; Xinjun Zhang; Baopeng Wang; Dongyu Hu; Dong Ren; Xiaolin Wang; Xiaofei Xia; et al. (Science Bulletin, 2025)

The combination of linkage mapping, genome-wide association study, and dynamic transcriptome analysis reveals conserved candidate genes for salt tolerance in maize - Ziyi Xiao; Zhenyuan Pan; Xinxin Liu; Xueqing Zheng; Guantao Wang; Yayu Fu; Mengmeng Li; Bin Hou; Xuhua Li; Ming Zhang; Chunlan Jia; Fazhan Qiu (Theoretical and Applied Genetics, 2025)

Trace element and sulfur isotope study of sulfide chimneys from the mafic-hosted Daxi Vent Field: Implications on the genesis of seafloor massive sulfide deposit at a segment end - Yejian Wang; Ming Yang; Xiqiu Han; Sven Petersen; Yiyang Cai; Xinkai Hu; Anxia Chen; Zhongyan Qiu; Xing Yu; Hang Hu; Matthias Frische; Honglin Li (Chemical Geology, 2025)

Identification and functional characterization of grass carp TRPV1 in facilitating GCRV infection - Zi-Yu Xie; Yang Xu; Qiu-Shi Zhang; Zhi-Ming Liu; Liang Hu; Wei Wang; Tiao-Yi Xiao; De-Liang Li; Xin-Yu Liang; Jun-Hua Li (Aquaculture, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Tenecteplase Plus Butyphthalide for Stroke Within 4.5–6 Hours of Onset (EXIT-BT): a Phase 2 Study - Hui-Sheng Chen; Ming-Rui Chen; Yu Cui; Xin-Yu Shen; Hong Zhang; Jiang Lu; Li-Wei Zhao; Ying-Jie Duan; Jing Li; Ya-Mei Wang; Lian-Qiu Min; Li-Hong Zhao; et al. (Translational Stroke Research, 2025)

Gold mineralization in the hydrothermal field at the termination of a detachment fault: A case study of the Tianxiu Vent Field - Ming Yang; Yejian Wang; Sven Petersen; Zhongyan Qiu; Honglin Li; Peng Zhou; Yiyang Cai; Xing Yu; Matthias Frische; Jiqiang Liu; Xiqiu Han (Mineralium Deposita, 2025)

Potential Enhancement in Anaerobic Digestion Performance of High Salinity Organic Wastewater with Nickel-Loaded Biochar - Chen-Shun Lu; Jin-Ming Qiu; Xiang Li; Hongyu Jiang; Yanlong Zhang; Yong Hu (International Journal of Environmental Research, 2025)

Dose-dependent inflammatory and neurotoxic effects of polypropylene microplastics in Nile tilapia evidenced by internal extractive electrospray ionization high-resolution mass spectrometry metabolomics - Xiaokang Wu; Susu Pan; Ming Li; Jiaxin Dong; Yining Wang; Chenni Huang; Tao Qiu; Yu Gu; Dapeng Liang (Environmental Chemistry Letters, 2025)

A novel electrochemical sensor for real-time quantitative monitoring of neuronal hydrogen peroxide under hypoxic conditions - Dan Su; Qianmin Li; Huihui Liang; Genhua Zhu; Ming Yang; Liangliang Liao; Zhaozhi Qiu; Youhui Zhang; Jiaquan Xu; Zhifu Ai; Yonggui Song (Chemical Engineering Journal, 2025)

Vertically oriented micron-thick perovskite film enables efficient and stable inverted perovskite solar cells - Bing-Hao Lv; Yong-Chun Ye; Jun-Gan Wang; Liu-Jiang Zhang; Yu-Hang Zhang; Ming-Li Zheng; Xian-Min Chen; Hui-Wei Du; Jie Yang; Xin-Yu Zhang; Meng-Lei Xu; Qiu-Feng Ye; et al. (Chemical Engineering Journal, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Removal and recovery of perchlorate from fireworks production wastewater through ion exchange and biological reduction processes - Jie Ma; Waseem ur Rahman; Peijun Du; Qimeng Li; Fei He; Guoyu Qiu; Guoxiang Wang; Xiaoguang Xu; Donglin Li; Ming Li; Shuizhong Lin (Journal of Environmental Management, 2025)

Pilot-scale demonstration of perchlorate-contaminated fireworks wastewater treatment through a combined ion-exchange and bioregeneration approach - Guoyu Qiu; Changkai Wang; Peijun Du; Qimeng Li; Fei He; Jie Ma; Donglin Li; Ming Li; Shuizhong Lin (Journal of Environmental Chemical Engineering, 2025)

Morphological characteristics and distribution of antennal sensilla of Spodoptera litura (Lepidoptera: Noctuidae) using scanning electron microscopy - Yong-Ping Li; Hai-Yan Zhou; Hui Ye; Robert A. Haack; Yuan Yang; Qiu-Lian Hu; Ming-Min Jiang; Jun Cao (Zoomorphology, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Estradiol Enhances Cerebellar Molecular Layer Interneuron-Purkinje Cell Synaptic Transmission and Improves Motor Learning Through ER-β in Vivo in Mice - Yong-Rui Piao; Mei-Rui Li; Ming-Ze Sun; Yang Liu; Chao-Yue Chen; Chun-Ping Chu; Yuki Todo; Zheng Tang; Chun-Yan Wang; Wen-Zhe Jin; De-Lai Qiu (The Cerebellum, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

DNA barcode reference database and gap analysis for biomonitoring Hong Kong’s marine animals - Mei-Hong Zhao; Jack Chi-Ho Ip; Chun Ming How; Yi-Xuan Li; Dumas Deconinck; Jian-Wen Qiu (Regional Studies in Marine Science, 2025)

Pyrite geochemistry and its implications for ore formation in reduced copper skarn systems: A case study of the Saibo deposit, Northwest China - Qing-Fei Sun; Ju-Xing Tang; Shun-Da Li; Qiu-Ming Pei; Xin-Hao Sun; Chuan Chen; Ling-Ling Gao; Xiao-Fei Du; Jin-Ling Xie (Chemical Geology, 2025)

DT-DDQNR: A digital twin assisted direct-to-cell satellite network intelligent routing algorithm - Wentao He; Huayi Li; Shi Qiu; Ming Liu; Xinyu Wang (Advances in Space Research, 2025)

Effect of borehole deviation on raise formation via long-hole raise blasting - Xianyang Qiu; Wenbo Shen; Xiuzhi Shi; Ming Tao; Xiaoyuan Li; Wei Zhi (Tunnelling and Underground Space Technology, 2024)

Preconception exposure to bisphenol A and its alternatives: Effects on female fecundity mediated by oxidative stress and ovarian reserve - Wei Qiu; Shengju Yin; Kadila Abulaiti; Xinyu Li; Yao Lu; Qianlong Zhang; Ming Zhan; Jun Zhang (Science of The Total Environment, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A transcriptomics-based analysis of mechanisms involved in the neurobehavioral effects of 6PPD-quinone on early life stages of zebrafish - Xuchun Qiu; Jie Tang; Yibing Zhang; Ming Li; Kun Chen; Yanhong Shi; Xiangyang Wu (Aquatic Toxicology, 2024)

Macroalgal fossil Longfengshania from the Tonian Shiwangzhuang and Jiuliqiao formations in western Shandong and northern Anhui, North China - Guang-Jin Li; Lei Chen; Ke Pang; Qing Tang; Cheng-Xi Wu; Rui Huang; Ming-Yang Qiu; Xun-Lai Yuan; Chuan-Ming Zhou (Palaeoworld, 2024)

Sludge-based biochar preparation: pyrolysis and co-pyrolysis methods, improvements, and environmental applications - Jun Cao; Yutong Jiang; Xiao Tan; Lei Li; Songshan Cao; Jiayao Dou; Runqi Chen; Xiaoyun Hu; Zhiheng Qiu; Ming Li; Ziyin Chen; Hualun Zhu (Fuel, 2024)

Dihydroartemisinin regulates the apoptosis and growth of colorectal cancer by suppressing DPYSL2 and increasing TF and ACHE - Xiao Zhang; Jun-Feng Cao; Dunshui Liao; Zengliang Xia; Li Xiong; Mei Wu; Chaochao Wang; Xingyu Yang; Yixin Qiu; Lixin Zhang; Ningbo Chen; Ming Zhang; et al. (Food Bioscience, 2024)

Decoding the biochemical dialogue: metabolomic insights into soybean defense strategies against diverse pathogens - Min Qiu; Mengjun Tian; Yaru Sun; Huaibo Li; Wenwen Huang; Haibing Ouyang; Shaoyan Lin; Chen Zhang; Ming Wang; Yuanchao Wang (Science China Life Sciences, 2024)

Rapid Real-Time Prediction Techniques for Ammonia and Nitrite in High-Density Shrimp Farming in Recirculating Aquaculture Systems - Fudi Chen; Tianlong Qiu; Jianping Xu; Jiawei Zhang; Yishuai Du; Yan Duan; Yihao Zeng; Li Zhou; Jianming Sun; Ming Sun (Fishes, 2024)
Water quality early warning is a key aspect in industrial recirculating aquaculture systems for high-density shrimp farming. The concentrations of ammonia nitrogen and nitrite in the water significantly impact the cultured animals and are challenging to measure in real-time, posing a substantial challenge to water quality early warning technology. This study aims to collect data samples using low-cost water quality sensors during the industrial recirculating aquaculture process and to construct predictive values for ammonia nitrogen and nitrite, which are difficult to obtain through sensors in the aquaculture environment, using data prediction techniques. This study employs various machine learning algorithms, including General Regression Neural Network (GRNN), Deep Belief Network (DBN), Long Short-Term Memory (LSTM), and Support Vector Machine (SVM), to build predictive models for ammonia nitrogen and nitrite. The accuracy of the models is determined by comparing the predicted values with the actual values, and the performance of the models is evaluated using Mean Absolute Error (MAE), Mean Absolute Percentage Error (MAPE), and Root Mean Square Error (RMSE) metrics. Ultimately, the optimized GRNN-based predictive model for ammonia nitrogen concentration (MAE = 0.5915, MAPE = 28.95%, RMSE = 0.7765) and the nitrite concentration predictive model (MAE = 0.1191, MAPE = 29.65%, RMSE = 0.1904) were selected. The models can be integrated into an Internet of Things system to analyze the changes in ammonia nitrogen and nitrite concentrations over time through aquaculture management and routine water quality conditions, thereby achieving the application of recirculating aquaculture system water environment early warning technology.

CRISPR-Cas9-mediated editing of GmARM improves resistance to multiple stresses in soybean - Tingting Luo; Chongxuan Ma; Yuanhang Fan; Zhendong Qiu; Ming Li; Yusu Tian; Yuzhuo Shang; Chang Liu; Qingqian Cao; Yuhan Peng; Shuzhen Zhang; Shanshan Liu; et al. (Plant Science, 2024)

Design and numerical simulation of the elastomeric support for the topside modules of an FPSO - Yucu Huang; Yanping He; Yadong Liu; Ming Qiu; Mingzhi Li (Ocean Engineering, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Plasmonic colorimetry and G-quadruplex fluorescence-based aptasensor: A dual-mode, protein-free and label-free detection for OTA - Ming Li; Youxin Qiu; Guoxing Liu; Yu Xiao; Ye Tian; Song Fang (Food Chemistry, 2024)

Forest disturbance thresholds on summer low flows in the interior of British Columbia, Canada - Yiping Hou; Xiaohua Wei; Jinyu Hui; Zhipeng Xu; Ming Qiu; Mingfang Zhang; Qiang Li; Qi Chen (CATENA, 2024)

Submerged macrophyte restoration enhanced microbial carbon utilization in shallow lakes - Yao Guo; Songsong Gu; Andrew J. Tanentzap; Pei Wang; Qianzheng Li; Kaixuan Wu; Peng He; Xiangfen Liu; Junqi Yu; Dongru Qiu; Junmei Wu; Yi Zhang; et al. (Science of The Total Environment, 2024)

Occurrence, seasonal variations, and fate of household and personal care chemicals in a wastewater treatment plant with Bacillus bioreactor process - Lin-Hui Zhang; Wen-Long Li; Zi-Feng Zhang; Xi-Ze Min; Ming-Gang Cai; Hang Xiao; Qing Diao; Zhen Qiu; Yi-Fan Li (Chemosphere, 2024)

Environmental perchlorate, thiocyanate, and nitrate exposures and bone mineral density: a national cross-sectional study in the US adults - Juxiao Li; Bohai Du; Yuhan Wang; Jiahuang Qiu; Ming Shi; Muhong Wei; Li Li (Environmental Science and Pollution Research, 2024)

Two new degrade triterpenoids from Buxus bodinieri Levl. - Yu-Xin Yan; Na-Li Song; Ji-Hong Zhang; Ming-Hua Qiu (Natural Product Research, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Biogenic manganese oxides promote metal(loid) remediation by shaping microbial communities in biological aqua crust - Guobao Wang; Zekai Feng; Xiuran Yin; Daijie Chen; Nan Zhao; Yongqiang Yuan; Chiyu Chen; Chong Liu; Ming Ao; Lei Chen; Ziwu Chen; Wenjun Yang; et al. (Water Research, 2024)

Simulation of vertical migration behaviors of heavy metals in polluted soils from arid regions in northern China under extreme weather - Zixin Xu; Ming Yin; Xue Yang; Yong Yang; Xuehui Xu; Haigang Li; Mei Hong; Guohong Qiu; Xionghan Feng; Wenfeng Tan; Hui Yin (Science of The Total Environment, 2024)

Gamma-ray irradiation as an effective method for mitigating antibiotic resistant bacteria and antibiotic resistance genes in aquatic environments - Ming-Qi Zhang; Xiao-Yong Zhang; Han-Chao Zhang; Hai-Bin Qiu; Zheng-Hao Li; Dong-Hua Xie; Li Yuan; Guo-Ping Sheng (Journal of Hazardous Materials, 2024)

Designing and preparing supramolecular encapsulation systems based on fraxetin and cyclodextrins for highly selective detection of nicotine - Yun-Han Yang; Zhen Zhang; Qiu-Lian Bao; Fang Zhao; Ming-Kun Yang; Xin Tao; Yan Chen; Jun-Tong Zhang; Li-Juan Yang (Carbohydrate Polymers, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Leucine improves dietary protein use efficiency by regulating protein synthesis by activating amino acid transporters and the mTORC1 pathways in Chinese mitten crab (Eriocheir sinensis) - Ming-Qi Song; Qiu-Ran Yu; Er-Chao Li; Ying Song; Xin-Yu Cai; Yu-Xiang Huang; Chuan-Jie Qin; Xiao-Dan Wang; Jian-Guang Qin; Li-Qiao Chen (Aquaculture, 2024)

Study of the wet-towing transportation of an FPSO with elastomeric-supporting topside modules - Yucu Huang; Yanping He; Ming Qiu; Yadong Liu; Mingzhi Li (Ocean Engineering, 2024)

LiDeNeRF: Neural radiance field reconstruction with depth prior provided by LiDAR point cloud - Pengcheng Wei; Li Yan; Hong Xie; Dashi Qiu; Changcheng Qiu; Hao Wu; Yinghao Zhao; Xiao Hu; Ming Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Leaching of heavy metals from tungsten mining tailings: A case study based on static and kinetic leaching tests - Xiaojun Zheng; Shiyue Qiu; Buchan Zhou; Qi Li; Ming Chen (Environmental Pollution, 2024)

Soil carbon turnover and balance in the priming effects of basalt, montmorillonite, and kaolinite in a Luvisol soil - Junyan Xu; Junli Liu; Qinglin Fu; Ming Zhang; Bin Guo; Hua Li; Xiaodong Chen; Gaoyang Qiu (Journal of Soils and Sediments, 2024)

Quaternary stratigraphic architecture of the Pearl River Mouth continental shelf, northern South China Sea: Unraveling stratigraphic imprints of tectonism, paleoceanography, and climate change - Haiteng Zhuo; Xin Nie; Ming Su; Wei Zhou; Yaping Lei; Yingmin Wang; Xuechao Peng; Yan Qiu; Weiyao Yan; Li'e Lin (Sedimentary Geology, 2024)

Garnet geochemistry reveals late-stage oxidation of tin-bearing fractionated granite - Jin-Xiang Li; Lin Ding; Noreen J. Evans; Fang Xu; Wei-Ming Fan; Li-Yun Zhang; Fu-Long Cai; Qiu-Yun Guan; Ya-Hui Yue; Jing Xie (Lithos, 2024)

Interaction between chromite and Mn(II/IV) under anoxic, oxic and anoxic-oxic conditions: Dissolution, oxidation and pH dependence - Ming Ao; Shengsheng Sun; Tenghaobo Deng; Jingjing Li; Ting Liu; Yetao Tang; Shizhong Wang; Rongliang Qiu (Journal of Environmental Management, 2024)

Release of chromium from Cr(III)- and Ni(II)-substituted goethite in presence of organic acids: Role of pH in the formation of colloids and complexes - Shengsheng Sun; Tenghaobo Deng; Ming Ao; Yijun Mo; Jingjing Li; Ting Liu; Wenjun Yang; Chao Jin; Rongliang Qiu; Yetao Tang (Science of The Total Environment, 2023)

Engineering high specific surface area over poly (ionic liquids)-derived molybdenum-silica hybrid materials for enhanced oxidative desulfurization - Tianqi Huang; Xiaofan Qiu; Linhua Zhu; Chao Wang; Hongping Li; Yiqun Fan; Ming Zhang; Huaming Li; Wenshuai Zhu (Journal of Environmental Chemical Engineering, 2023)

Discovery of the large-scale Eocene Xiwu Pb–Zn–Ag deposit in the Tethyan Himalaya: Geochronology, geochemistry, and C–H–O–S–Pb–Sr–Nd isotopes - Hua-Wen Cao; Qiu-Ming Pei; Xiao Yu; M. Santosh; Guang-Ming Li; Lin-Kui Zhang; Hao Zou; Lei Dong; Ke Gao; Zuo-Wen Dai; Jin-Biao Ai; Shuang-Shuang Lan; et al. (Gondwana Research, 2023)

Genomic and biogenic amine-reducing characterization of Lactiplantibacillus planatraum JB1 isolated from fermented dry sausage - Shan Qin; Xian Ming Zeng; Mei Jiang; Xin Rui; Wei Li; Ming Sheng Dong; Xiao Hong Chen; Qiu Qin Zhang (Food Control, 2023)

Insights into the antibacterial activity and antibacterial mechanism of silver modified fullerene towards Staphylococcus aureus by multiple spectrometric examinations - Yin-Xu Pan; Qiu-Hui Xu; Hua-Ming Xiao; Chun-Ya Li (Chemosphere, 2023)

Dissolved inorganic carbon budget of two alpine catchments in the central Tibetan Plateau: Glaciation matters - Zhengliang Yu; Jianhong Li; Guangjian Wu; Dongmei Qu; Fei Wang; Xiaoxing Ming; Haiying Qiu; Zhu Liu; Philipp Maurischat (Science of The Total Environment, 2023)

Perovskites with narrow quantum-wells distribution and thermally activated energy funneling for sky-blue light-emitting diodes - Guanwei Sun; Weidong Qiu; Jiayu Li; Shuai Zhang; Zijian Chen; Denghui Liu; Chenyang Shen; Tao Wen; Zhe Liu; Junrong Pu; Zhihai Yang; Guo-xi Yang; et al. (Chemical Engineering Journal, 2023)

Efficacy of a porcine reproductive and respiratory syndrome virus 1 (PRRSV-1) natural recombinant against a heterologous PRRSV-1 isolate both clustered within the subgroup of BJEU06-1-like isolates - Chen Li; Shuai Li; Shubin Li; Ming Qiu; Hong Lin; Zhe Sun; Yuejia Qiu; Wenhao Qi; Binghui Feng; Jixiang Li; Wanglong Zheng; Xiuling Yu; et al. (Veterinary Microbiology, 2023)

A review of anaerobic granulation under high-salinity conditions: Mechanisms, influencing factors and enhancement strategies - Chen-Shun Lu; Jin-Ming Qiu; Yang Yang; Yong Hu; Yu-You Li; Takuro Kobayashi; Yong-Jun Zhang (Journal of Water Process Engineering, 2023)

Polyurethane sponge loading improves the suspension of magnetic materials without affecting the Pb(Ⅱ) adsorption - Ruifeng Li; Guihong Lan; Yongqiang Liu; Qiao Sun; Bin Luo; Ming Zhang; Haiyan Qiu; Bo Xu; Chunping Deng (Journal of Environmental Chemical Engineering, 2023)

Exploration of glycosyltransferases mutation status in cervical cancer reveals PARP14 as a potential prognostic marker - Hui Wang; Shen Luo; Xin Wu; Yuanyuan Ruan; Ling Qiu; Hao Feng; Shurong Zhu; Yanan You; Ming Li; Wenting Yang; Yanding Zhao; Xiang Tao; et al. (Glycoconjugate Journal, 2023)
This study investigates the potential role of Glycosyltransferases (GTs) in the glycosylation process and their association with malignant tumors. Specifically, the study focuses on PARP14, a member of GTs, and its potential as a target for tumors in the diagnosis and treatment of cervical cancer. To gather data, the study used somatic mutation data, gene expression data and clinical information from TCGA-CESE dataset as well as tissue samples from cervical cancer patients. Further verification was conducted through RT-qPCR and immunohistochemistry staining on cervical cancer tissues to confirm the expression of PARP14. The study utilized Kaplan-Meier for survival analysis of cervical cancer patient and found significant mutational abnormalities in GTs. The high frequency mutated gene was identified as PARP14. RT-qPCR revealed significantly higher mRNA expression of PARP14 compared to precancerous tissue. Using IHC combined with Kaplan-Meier,patients in the PARP14 high expression group had a better prognosis than the low expression group. The study identified PARP14 as a frequently mutated gene in cervical cancer and proposed its potential role in diagnosis and treatment.

Construction of covalent organic framework nanozymes with photo-enhanced hydrolase activities for colorimetric sensing of organophosphorus nerve agents - Sai-Jin Xiao; Ming-Yue Yuan; Ya-Di Shi; Meng-Ping Wang; Hui-Han Li; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Nano zero-valent iron enhances the absorption and transport of chromium in rice (Oryza sativa L.): Implication for Cr risks management in paddy fields - Ting Liu; Zeting Guan; Jingjing Li; Ming Ao; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Non-monotonic Association Between Chlorinated Polyfluorinated Ether Sulfonic Acids Exposure and the Risk of Overweight/Obesity Status in Adults - Chu Chu; Qiu-Ling Fang; Xin-Xin Cui; Peng-Xin Dong; Zhengmin Qian; Stephen Edward McMillin; Steven W. Howard; Yan-Qiu Ou; Qing-Qing Li; Lu-Yin Wu; Li-Xia Liang; Shuang-Jian Qin; et al. (Exposure and Health, 2023)

System design and operation optimization on the hybrid system with nuclear power, concentrated solar, and thermal storage - Binbin Qiu; Ganggang Li; Xin Wei; Ming Liu; Junjie Yan (Annals of Nuclear Energy, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Applying mass flow analysis and aeration optimization strategy to reduce energy consumption of a full-scale anaerobic/anoxic/oxic system - Lu-Man Jiang; Wen Zhang; Yunhui Li; Yanjun Shao; Zhenjian Zhang; Ming Zhang; Junli He; Ji Qiu; Wenxiang Li; Junwei Wang; Zhen Zhou (Journal of Water Process Engineering, 2023)

Bioremediation of aniline aerofloat wastewater at extreme conditions using a novel isolate Burkholderia sp. WX-6 immobilized on biochar - Jin-Cheng Ye; Qiu-Shi Zhao; Jin-Wei Liang; Xiao-Xiao Wang; Zhen-Xuan Zhan; Huan Du; Ji-Liang Cheng; Lei Xiang; Nai-Xian Feng; Bai-Lin Liu; Yan-Wen Li; Hui Li; et al. (Journal of Hazardous Materials, 2023)

Quantifying source effects based on rainwater δ18O from 10-year monitoring records in Southwest China - Yan-Xia Xue; Jian Zhang; Zhen Su; Yao Wu; Qi-sheng Liang; Ming-Qiang Liang; Xiang-Zhuo Liu; Chao-Jun Chen; Hai-Ying Qiu; Jun-Yun Li; Ting-Yong Li (Applied Geochemistry, 2023)

Effect of Bacillus amyloliquefaciens LSG2 ‐8 on the intestinal barrier function of Amur minnow ( Rhynchocypris lagowskii ) - Meng‐Nan Yu; Wen‐li Zhu; Si‐bu Wang; Dong‐Ming Zhang; Yu‐Rou Zhang; Qiu‐Ju Wang; Gui‐Qin Wang; Mahmoud M. Elsadek; Qi Yao; Yu‐Ke Chen; Zhi‐Xin Guo (Journal of Fish Biology, 2023)
Probiotics are widely used in aquaculture. This article aims to study the effect of Bacillus amyloliquefaciens LSG2‐8 on the intestinal barrier function of Rhynchocypris lagowskii. B. amyloliquefaciens LSG2‐8 were added to R. lagowskii basal diets (CK) as additives at four concentrations: 1.0 × 10 6 (D‐6), 1.0 × 10 7 (D‐7), 1.0 × 10 8 (D‐8) and 1.0 × 10 9 (D‐9) CFU g −1 by dry weight of basal diet. After a 56‐day feeding experiment, the activities of intestinal digestive enzymes and immunity‐related enzymes of R. lagowskii on group D‐6, D‐7, D‐8 and D‐9 diet were significantly higher than the control ( P R. lagowskii were significantly higher ( P R. lagowskii on group D‐6, D‐7, D‐8 and D‐9 diet were significantly lower than those of the control ( P B. amyloliquefaciens LSG2‐8 can regulate the intestinal flora balance and improve the intestinal structure of R. lagowskii . In conclusion, B. amyloliquefaciens LSG2‐8 can improve the intestinal barrier function of R. lagowskii and can be used as a feed additive in aquaculture.

A systematic review: on the mercaptoacid metabolites of acrylamide, N-acetyl-S-(2-carbamoylethyl)-L-cysteine - Fang-Fang Zhao; Xiao-Li Wang; Ya-Ting Lei; Hong-Qiu Li; Zhi-Ming Li; Xiao-Xiao Hao; Wei-Wei Ma; Yong-Hui Wu; Sheng-Yuan Wang (Environmental Science and Pollution Research, 2023)

Machine learning models to predict the tunnel wall convergence - Jian Zhou; Yuxin Chen; Chuanqi Li; Yingui Qiu; Shuai Huang; Ming Tao (Transportation Geotechnics, 2023)

Synergistic effects of pyrolysis temperature, iron ion concentration and solid/liquid ratio on the properties and Cr(VI) removal performance of magnetic carbon - Qiang Qu; Ling Qiu; Ming-Zhuo Li; Guo-Tao Sun; He-Yu Chen; Xiao-Hui Guo (Journal of Water Process Engineering, 2023)

Beta-naphthoflavone increases the differentiation of osteoblasts and suppresses adipogenesis in human adipose derived stem cells involving STAT3 pathway - Ming Lu; Min Li; Tao Luo; Yongsui Li; Mingxin Wang; Huashi Xue; Mengchen Zhang; Qiu Chen (Molecular & Cellular Toxicology, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Comparative transcriptomes analysis of the ovary reveals potential ovarian development-related genes and pathways in Macrobrachium rosenbergii - Yan-Hao Yang; Rui Wang; Ming Li; Hui-Zan Yang; Guang-Hua Huang; Ke-Yi Ma; Gao-Feng Qiu; Yong Lin (Invertebrate Reproduction & Development, 2023)

Biofilter-constructed wetland-trophic pond system: A new strategy for effective sewage treatment and agricultural irrigation in rural area - Xinxin Peng; Wei Yang; Qiu Jin; Shihua Su; Pan Guo; Ming Li; Huazu Liu; Wei Li (Journal of Environmental Management, 2023)

Inhibiting Cyclin B1-treated Pontine Infarction by Suppressing Proliferation of SPP1+ Microglia - Ming Luo; Zhihua Qiu; Xiangyue Tang; Li Wu; Shaojun Li; Juehua Zhu; Yongjun Jiang (Molecular Neurobiology, 2023)

Inhibition of ferroptosis by icariin treatment attenuates excessive ethanol consumption-induced atrial remodeling and susceptibility to atrial fibrillation, role of SIRT1 - Li-Ming Yu; Xue Dong; Tao Huang; Ji-Kai Zhao; Zi-Jun Zhou; Yu-Ting Huang; Yin-Li Xu; Qiu-Sheng Zhao; Zhi-Shang Wang; Hui Jiang; Zong-Tao Yin; Hui-Shan Wang (Apoptosis, 2023)

Low-noise, low-power-consumption seafloor vector magnetometer - Xiaochen Li; Xianhu Luo; Ming Deng; Ning Qiu; Zhen Sun; Kai Chen (Journal of Oceanology and Limnology, 2023)

Performance and mechanism of sacrificed iron anode coupled with constructed wetlands (E-Fe) for simultaneous nitrogen and phosphorus removal - Ming Zhou; Jiashun Cao; Yuanyuan Qiu; Yanhong Lu; Jinyan Guo; Chao Li; Yantang Wang; Liangshan Hao; Hongqiang Ren (Environmental Science and Pollution Research, 2023)

Biotransformation of sulfamonomethoxine in a granular sludge system: Pathways and mechanisms - Meng-Yuan Li; Run-Dong Zhang; Yi-Xing Lin; Qi-Wen Li; Qiu-Yue Zhao; Zong-Xi Zhao; Zhong-Ming Ling; Long-Fei Shu; Min Zhang; Li-Xin Hu; Yi-Jing Shi; Guang-Guo Ying (Chemosphere, 2023)

ARSCP: An antimicrobial residue surveillance cloud platform for animal-derived foods - Jun-Jun Yu; Ya-Lin Hu; Cheng-Zheng Liu; Shuai-Bin Wu; Zi-Jian Zheng; Ze-Hua Cui; Li Chen; Tian Wei; Shi-Kai Sun; Jun Ning; Xiang Wen; Qiu-Yue Diao; et al. (Science of The Total Environment, 2023)

Treatment and remediation of metal-contaminated water and groundwater in mining areas by biological sulfidogenic processes: A review - Yu Li; Qingxia Zhao; Ming Liu; Jiahua Guo; Juntao Xia; Jinting Wang; Yanying Qiu; Jiahui Zou; Weiting He; Feng Jiang (Journal of Hazardous Materials, 2023)

Boosting the hydrogen evolution of layered double hydroxide by optimizing the electronic structure and accelerating the water dissociation kinetics - Hongbo He; Jiayong Xiao; Zhibin Liu; Bin Yang; Dashuai Wang; Xianyun Peng; Libin Zeng; Zhongjian Li; Lecheng Lei; Ming Qiu; Yang Hou (Chemical Engineering Journal, 2023)

Highly efficient polyhydroxyalkanoate production from lignin using genetically engineered Halomonas sp. Y3 - Yuan-Qiu Li; Ming-Jun Wang; Chao-Bing Luo (Bioresource Technology, 2023)

Huntingtin-associated protein 1 is a potential tumor suppressor for gastric cancer - Ye-Min Qu; Ai Chen; Xue Zhao; Zan Wang; Dong Guo; Shu-Li Shao; Yuan-Yong Tao; Qiu-Jing Li; Ming-Yi Wang; Wan-Shan Ma (Molecular Biology Reports, 2023)

Black soldier fly larvae replace traditional iced trash fish diet to enhance the delicious flavor of Chinese mitten crab (Eriocheir sinensis) - Jian-Feng Qiu; Cheng Luo; Li-Hua Ren; Wei Li; Tai-Ming Dai; Guang Wang; Xiao-Ning Sun; Kou-Chang Chong Moua; Yang-Hu Sima; Shi-Qing Xu (Frontiers in Marine Science, 2023)
Chinese mitten crabs ( Eriocheir sinensis ) are traditionally fed iced trash fish, but the industry is facing problems such as low breeding safety. Black soldier fly ( Hermetia illucens ) is an alternative protein source in animal diets, including diets for aquatic animals, due to its high nutritional value. However, studies on the effects of black soldier fly on the flavor characteristics of aquatic animals are still limited. In the present study, we investigated the effects of the complete replacement of iced trash fish with black soldier fly larvae during the fattening period of Chinese mitten crab on the flavor molecule contents and evaluation indices. The levels of free amino acids and nucleotides were determined in three edible parts (muscle, hepatopancreas, and gonads) of crab. Taste activity value analysis showed that glutamic acid, glycine, alanine, and arginine were the main amino acids contributing to the umami taste and sweetness, while histidine, lysine, valine, and methionine were the main amino acids contributing to the bitterness. Equivalent umami concentration (EUC) analysis showed that female gonads had the strongest umami taste, followed by the hepatopancreas and muscle. Sweetness value (SWT) analysis showed that the sweetness of muscle was the highest. Feeding black soldier fly larvae affected the flavor characteristics of crabs with tissue and sex differences. The EUC of the female gonads and SWT of the muscle were significantly increased. Meanwhile, the EUC of the hepatopancreas and SWT of the gonads were slightly decreased in male crabs. Our results indicate that the complete replacement of iced trash fish with black soldier fly larvae during the fattening period significantly enhances the flavor characteristics of crabs based on the contents of flavoring amino acids and nucleotides. It is important for sustainable aquaculture to replace animal protein with alternative protein sources such as black soldier fly larvae.

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Cleaner 2,3-butanediol production from unpretreated lignocellulosic biomass by a newly isolated Klebsiella pneumoniae PX14 - Yuan-Qiu Li; Ming-Jun Wang; Xiao-Feng Gan; Chao-Bing Luo (Chemical Engineering Journal, 2023)

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis - Long Liu; Feng-Ming Yan; Chen-Chen Zhao; Li-Juan Su; Qiu-Ying Huang; Qing-Bo Tang (Journal of Pest Science, 2023)
Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1 , drive social immunity in insect colonies is still unknown. Here, we used a ‘host–pathogen’ system (host: Reticulitermes chinensis ; pathogen: Metarhizium anisopliae ) to explore the impact of miRNAs on social immunity in termite colonies. We found that RNAi-mediated silencing of Dicer-1 led to decreased miRNA concentration, significantly inhibited carbohydrate and energy metabolism and affected other life processes, such as the immune response and oxidation–reduction reactions, in whole body of the termite. In behavioural defence, silencing Dicer-1 significantly diminished defensive social behaviours such as locomotion, grooming, cannibalism and burial in termite groups when encountering fungal contamination. In physiological defence, Dicer-1 silencing and miR-71-5 stimulation resulted in significantly decreased antifungal activities of termites. Furthermore, both Dicer-1 -silenced and miR-71-5 stimulant-treated termite groups exhibited a high level of mortality during fungal contamination. Our findings demonstrated the important role of miRNAs in shaping social immunity in termite colonies, providing insights necessary to understand the potential mechanisms underlying behavioural and physiological disease defences in insects and hence laying the groundwork for miRNA-based pest control.

Zinc supplementation ameliorates sorafenib-induced cognitive impairment through ROS/JNK signaling pathway - Can-Can Zhou; Yu-Qiong He; Yu-Shuang Qiu; Chen-Xu Ni; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2023)

Cultivation of Haematococcus pluvialis in source-separated urine for biomass production and astaxanthin accumulation - Guan-qiu Ma; Li-hua Li; Yu Hong; Ming-ran Yu (Algal Research, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Exploration of the amino acid metabolic signature in anthracycline-induced cardiotoxicity using an optimized targeted metabolomics approach based on UPLC-MS/MS - Wendi Li; Shanshan Li; Zhenju Cao; Yi Sun; Wei Qiu; Mei Jia; Ming Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

Dietary supplementation of two indigenous Bacillus spp on the intestinal morphology, intestinal immune barrier and intestinal microbial diversity of Rhynchocypris lagowskii - Xin-yu Lei; Dong-ming Zhang; Qiu-ju Wang; Gui-qin Wang; Yue-hong Li; Yu-rou Zhang; Men-nan Yu; Qi Yao; Yu-ke Chen; Zhi-xin Guo (Fish Physiology and Biochemistry, 2022)

Adsorption properties and mechanism research of phosphorus with different molecular structures from aqueous solutions by La-modified biochar - Ming-yao Yuan; Shang-kai Qiu; Meng-meng Li; Yuan Li; Ji-Xiu Wang; Yuan Luo; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2022)

Aquapteridospora jiangxiensis, a new aquatic hyphomycetous fungus from a freshwater habitat in China - Su-Qin Peng; Yu-Lin Liu; Jun-En Huang; Xiao-Hong Li; Xin-Yi Yan; Hai-Yan Song; Yang Gao; Zhi-Jun Zhai; Yuan-Qiu Liu; Dian-Ming Hu (Archives of Microbiology, 2022)

Salprzesides A and B: two novel icetexane diterpenes with antiangiogenic activity from Salvia przewalskii Maxim - Bei-Ming Qiu; Pan Wang; Jie Li (Natural Product Research, 2022)

Two new compounds from a mangrove sediment-derived fungus Penicillium polonicum H175 - Shun-Zhi Liu; Xi-Xiang Tang; Feng-Ming He; Jian-Xin Jia; Hang Hu; Bao-Ying Xie; Ming-Yu Li; Ying-Kun Qiu (Natural Product Research, 2022)

Recent Developments in the Determination of PM2.5 Chemical Composition - Susu Pan; Yanting Qiu; Ming Li; Zhenqi Yang; Dapeng Liang (Bulletin of Environmental Contamination and Toxicology, 2022)

Phenotypic plasticity of light use favors a plant invader in nitrogen‐enriched ecosystems - Xiao Xu; Chenhao Zhou; Qiang He; Shiyun Qiu; Yan Zhang; Ji Yang; Bo Li; Ming Nie (Ecology, 2022)
Eutrophication is believed to promote plant invasion, resulting in high growth performances of invasive plants and, therefore, the great potential for growth‐induced intraspecific competition for light. Current hypotheses predict how eutrophication promotes plant invasion but fail to explain how great invasiveness is maintained under eutrophic conditions. In diverse native communities, co‐occurring plants of varying sizes can avoid light competition by exploiting light complementarily; however, whether this mechanism applies to intraspecific competition in invasive plant populations remains unknown. Using a 2‐year field nitrogen (N)‐enrichment experiment on one of the global invasive plants, Spartina alterniflora , we found that the plasticity of light use reduced intraspecific competition and increased biomass production in S. alterniflora . This plasticity effect was enhanced when S. alterniflora had no nutrient limitations. In the N‐enrichment treatments, the height difference among S. alterniflora ramets increased as light intensity decreased under the canopy. Compared with ambient N, under N enrichment, shorter individuals increased their light‐use efficiency and specific leaf area in response to the reduced light intensity under the canopy. However, such ecophysiological plasticity was not found for taller individuals. Our findings revealed that the light‐use plasticity of short individuals can be envisaged as a novel mechanism by which an invasive plant alleviates intraspecific competition and increases its invasiveness, challenging the prevailing perspective that the invasiveness of exotic plants is constrained by intraspecific competition.

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Deciphering the influence of urinary microbiota on FoxP3+ regulatory T cell infiltration and prognosis in Chinese patients with non-muscle-invasive bladder cancer - Yifeng Qiu; Yubo Gao; Chunxiao Chen; Ming Xie; Pengcheng Huang; Qi Sun; Zhipeng Zhou; Biao Li; Jie Zhao; Peng Wu (Human Cell, 2022)

Morphological and Molecular Characterization of Paragonimus skrjabini Complex from Yunnan, China: A Brief Report - Qiu-Hong Shu; Shu-De Li; Ming Tian; Yong Meng; Shu-Mei-Qi He; Min Zhu; Miao-Miao Wang; Wen-Lin Wang (Acta Parasitologica, 2022)
Purpose To perform environmental sampling and molecular identification of Paragonimus in endemic regions, which may help in minimizing transmission among humans. Methods Mountain crabs from the genus Potamiscus were collected and the encysted metacercariae were extracted and subjected to morphological identification, followed by animal inoculation in Sprague–Dawley (SD) rats. After 112 days of infection, animals were killed and adult worms were extracted from lungs and muscles. The morphology of adult worms was characterized by microscopy and molecular identification was done by polymerase chain reaction, followed by sequencing of cox1 and ITS2 genes. Phylogenetic analysis was done by maximum parsimony method. Results A total of 447 crabs were captured from the streams of Tongchang Town, Jinping County, Yunnan Province, China. The infection rate was found to be 41% (186 out of 447 crabs). The metacercariae of Paragonimus skrjabini was identified by the characteristics round or spherical encysted form measuring 410 to 460 × 400 to 460 µm. After animal infection in SD rats, adults were presumptively confirmed to be P. skrjabini , which was also confirmed by gene amplification and sequence analysis of cox1 and ITS2 regions. Paragonimus skrjabini clustered with previously reported P. skrjabini from Yunnan and Vietnam. The confidence values of their branches were > 95%. Phylogenetic analysis of the ITS2 region revealed two distinct clusters with distinct geographical grouping. Phylogenetic analysis with the combined data sets reiterated the geographical grouping with P. skrjabini from Yunnan clustering with strains from Vietnam. Conclusion Metacercariae of P. skrjabini was discovered in freshwater crabs in Yunnan province, China, and the strains were phylogenetically related to P. skrjabini from Vietnam.

Using computational fluid dynamic simulation with Flow-3D to reveal the origin of the mushroom stone in the Xiqiao Mountain of Guangdong, China - Jian-cheng Li; Wei Wang; Yan-ming Zheng; Xiao-hao Wen; Jing Feng; Li Sheng; Chen Wang; Ming-kun Qiu (Journal of Mountain Science, 2022)

Bioactive compounds derived from the marine-derived fungus MCCC3A00951 and their influenza neuraminidase inhibition activity in vitro and in silico - Shun-Zhi Liu; Feng-Ming He; Yan-lin Bin; Chu-Fang Li; Bao-Ying Xie; Xi-Xiang Tang; Ying-Kun Qiu (Natural Product Research, 2021)

Inhibition of Maternal c-Src Ameliorates the Male Offspring Hypertension by Suppressing Inflammation and Neurotransmitters in the Paraventricular Nucleus - Qing Su; Xiao-Jing Yu; Qing Yang; Xiao-Min Wang; Wen-Jie Xia; Hong-Bao Li; Kai-Li Liu; Qiu-Yue Yi; Yu-Ming Kang (Cardiovascular Toxicology, 2021)

Cysestermerol A, a rare stilbene sestermer with significant hypoglycemic activities from Cynodon dactylon - Feng Wang; Li Zhang; Bi-Jun Li; Qiu-Ming Liang; A-Li Chen; Zhen-Feng Fang; Shu-Mei Wang (Natural Product Research, 2021)

A fungal sirtuin modulates development and virulence in the insect pathogen, Beauveria bassiana - Qing Cai; Li Tian; Jia‐Tao Xie; Qiu‐Ying Huang; Ming‐Guang Feng; Nemat O. Keyhani (Environmental Microbiology, 2021)
Summary Chromatin transitions are mediated in part by acetylation/deacetylation post‐translational modifications of histones. Histone deacetylases, e.g. sirtuins (Sir‐proteins), repress transcription via promotion of heterochromatin formation. Here, we characterize the Sir2 class III histone deacetylase ( BbSir2 ) in the environmentally and economically important fungal insect pathogen, Beauveria bassiana . BbSir2 is shown to contribute to the deacetylation of lysine residues on H3 and H4 histones. Targeted gene knockout of BbSir2 resulted in impaired asexual development, reduced abilities to utilize various carbon/nitrogen sources, reduced tolerance to oxidative, heat, and UV stress, and attenuated virulence. ΔBbSir2 cells showed disrupted cell cycle development and abnormal hyphal septation patterns. Proteomic protein acetylation analyses of wild type and ΔBbSir2 cells revealed the differential abundance of 462 proteins and altered (hyper‐ or hypo‐) acetylation of 436 lysine residues on 350 proteins. Bioinformatic analyses revealed enrichment in pathways involved in carbon/nitrogen metabolism, cell cycle control and cell rescue, defence and mitochondrial functioning. Critical targets involved in virulence included LysM effector proteins and a benzoquinone oxidoreductase implicated in detoxification of cuticular compounds. These data indicate broad effects of BbSir2 on fungal development and stress response, with identification of discrete targets that can account for the observed (decreased) virulence phenotype.

Vertical Profiles of Volatile Organic Compounds in Suburban Shanghai - Yuhan Liu; Hongli Wang; Shengao Jing; Ming Zhou; Shenrong Lou; Kun Qu; Wanyi Qiu; Qian Wang; Shule Li; Yaqin Gao; Yusi Liu; Xiaobing Li; et al. (Advances in Atmospheric Sciences, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Correction to: Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Bai; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Central Blockade of E-Prostanoid 3 Receptor Ameliorated Hypertension Partially by Attenuating Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus of Spontaneously Hypertensive Rats - Fang-Fang Wang; Juan Ba; Xiao-Jing Yu; Xiao-Lian Shi; Jin-Jun Liu; Kai-Li Liu; Li-Yan Fu; Qing Su; Hong-Bao Li; Kai B. Kang; Qiu-Yue Yi; Shu-Qiu Wang; et al. (Cardiovascular Toxicology, 2021)

Modes of genetic adaptations underlying functional innovations in the rumen - Xiangyu Pan; Yudong Cai; Zongjun Li; Xianqing Chen; Rasmus Heller; Nini Wang; Yu Wang; Chen Zhao; Yong Wang; Han Xu; Songhai Li; Ming Li; et al. (Science China Life Sciences, 2021)

Sulfide ore prospecting in carbon-containing stratum using comprehensive time-domain induced polarization and controlled-source audio-frequency magnetotellurics - Ren-Bin Sun; Li-Xia Chu; Gui-Bin Zhang; Qiu-Ming Cheng; Yun-Chuan Xiang; Bin Hu; Chang-Rong Zhang; Jian-Fu Li; Yi-Jun Zhao (Applied Geophysics, 2020)

Phaeotremella camelliae sp. nov. (Phaeotremellaceae, Tremellales), A Novel Yeasts Isolated from Tea-Oil Fruits in Jiangxi Province, China - Yong Sun; Gui-Shuang Wang; Ai-Hua Li; Wangmu; Xian-Qiu Chui; Ji-Hong Jiang; Qi-Ming Wang (Current Microbiology, 2020)

Early use of dexamethasone increases Nr4a1 in Kupffer cells ameliorating acute liver failure in mice in a glucocorticoid receptor-dependent manner - Jing-wen Deng; Qin Yang; Xiao-peng Cai; Jia-ming Zhou; Wei-gao E; Yan-dong An; Qiu-xian Zheng; Meng Hong; Yan-li Ren; Jun Guan; Gang Wang; Shu-jing Lai; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Intrusion of Fall Armyworm (Spodoptera frugiperda) in Sugarcane and Its Control by Drone in China - Xiu-Peng Song; Yong-Jian Liang; Xiao-Qiu Zhang; Zhen-Qiang Qin; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Effects of Spray Parameters of Drone on the Droplet Deposition in Sugarcane Canopy - Xiao-Qiu Zhang; Xiu-Peng Song; Yong-Jian Liang; Zhen-Qiang Qin; Bao-Qing Zhang; Jin-Ju Wei; Yang-Rui Li; Jian-Ming Wu (Sugar Tech, 2020)

Angiotensin Type 1 Receptors and Superoxide Anion Production in Hypothalamic Paraventricular Nucleus Contribute to Capsaicin-Induced Excitatory Renal Reflex and Sympathetic Activation - Yun Qiu; Fen Zheng; Chao Ye; Ai-Dong Chen; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

Blockade of c-Src Within the Paraventricular Nucleus Attenuates Inflammatory Cytokines and Oxidative Stress in the Mechanism of the TLR4 Signal Pathway in Salt-Induced Hypertension - Qing Yang; Xiao-Jing Yu; Qing Su; Qiu-Yue Yi; Xin-Ai Song; Xiao-Lian Shi; Hong-Bao Li; Jie Qi; Guo-Qing Zhu; Yu-Ming Kang (Neuroscience Bulletin, 2020)

Phytochemicals and biological activities of species from the genus Maytenus - Lei Zhang; Ming-Yue Ji; Bin Qiu; Qin-Yu Li; Ke-Yong Zhang; Ji-Cheng Liu; Lian-Sheng Dang; Min-Hui Li (Medicinal Chemistry Research, 2020)

Chemical Stimulation of Renal Tissue Induces Sympathetic Activation and a Pressor Response via the Paraventricular Nucleus in Rats - Chao Ye; Yun Qiu; Feng Zhang; Ai-Dong Chen; Hong Zhou; Jue-Jin Wang; Qi Chen; Yue-Hua Li; Yu-Ming Kang; Guo-Qing Zhu (Neuroscience Bulletin, 2020)

The false smut pathogen Ustilaginoidea virens requires rice stamens for false smut ball formation - Jing Fan; Jie Liu; Zhi‐You Gong; Pei‐Zhou Xu; Xiao‐Hong Hu; Jin‐Long Wu; Guo‐Bang Li; Juan Yang; Yu‐Qiu Wang; Yu‐Feng Zhou; Shuang‐Cheng Li; Li Wang; et al. (Environmental Microbiology, 2020)
Summary Rice false smut has emerged as a serious grain disease in rice production worldwide. The disease is characterized by the transformation of individual rice florets into false smut balls, which is caused by the fungal pathogen Ustilaginoidea virens . To date, little is known about the host factors required for false smut ball formation by U . virens . In this study, we identified histological determinants for the formation of false smut balls by inoculating U . virens into rice floral mutants defective with respect to individual floral parts. The results showed that U . virens could form mature false smut balls in rice floral mutants with defective pistils, but failed to develop false smut balls in the superwoman mutant lacking stamens, identifying that U . virens requires rice stamens to complete its infection cycle. Comparative transcriptome analysis indicated a list of candidate host genes that may facilitate nutrient acquisition by U . virens from the rice stamens, such as SWEET11 , SWEET14 and SUT5 , and genes involved in the biosynthesis of trehalose and raffinose family sugars. These data pinpoint rice stamens as the key target organ of U . virens infection and provide a valuable starting point for dissecting the molecular mechanism of false smut ball formation.

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Isolation, structural elucidation and in vitro hepatoprotective activity of flavonoids from Glycyrrhiza uralensis - Ming Cheng; Liqin Ding; Hongfeng Kan; Hongmin Zhang; Benke Jiang; Yingjie Sun; Shijie Cao; Wei Li; Kazuo Koike; Feng Qiu (Journal of Natural Medicines, 2019)

Population structure and genetic diversity of Vibrio parahaemolyticus from a coastal area of China based on a multi-locus sequence typing (MLST) scheme - Yu Li; Hong-Qiu Yin; Jun Xia; Hong Luo; Ming-Yi Wang (Antonie van Leeuwenhoek, 2019)

Regulation of osteoblast behaviors via cross-talk between Hippo/YAP and MAPK signaling pathway under fluoride exposure - Wen-qing Zhu; Ying-juan Yu; Li-na Xu; Pan-pan Ming; Shui-yi Shao; Jing Qiu (Journal of Molecular Medicine, 2019)

Potential effects of exploiting the Yunfu pyrite mine (southern China) on soil: evidence from analyzing trace elements in surface soil - Zhi-hua Tang; Ting-ping Ouyang; Ming-kun Li; Ning-sheng Huang; Yao-qiu Kuang; Qiao Hu; Zhao-yu Zhu (Environmental Monitoring and Assessment, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Provenance of the Langjiexue Group to the south of the Yarlung-Tsangpo Suture Zone in southeastern Tibet: Insights on the evolution of the Neo-Tethys Ocean in the Late Triassic - Da-Ren Fang; Gen-Hou Wang; Ken-ichiro Hisada; Guo-Li Yuan; Fang-Lin Han; Dian Li; Yu Tang; Qiu-Ming Pei; Liang-Liang Zhang (International Geology Review, 2019)

Geochemistry, zircon U–Pb geochronology and Hf isotopes of Jurassic-Cretaceous granites in the Tengchong terrane, SW China: implications for the Mesozoic tectono-magmatic evolution of the Eastern Tethyan Tectonic Domain - Hua-Wen Cao; Yun-Hui Zhang; Li Tang; Steven P. Hollis; Shou-Ting Zhang; Qiu-Ming Pei; Chang Yang; Xiao-Shuan Zhu (International Geology Review, 2019)

Preparation of ion exchange resin using soluble starch and acrylamide by graft polymerization and hydrolysis - Ming Zhang; Guihong Lan; Haiyan Qiu; Tailiang Zhang; Wenjing Li; Xiuqiong Hu (Environmental Science and Pollution Research, 2019)

Cloning and Identification of Differentially Expressed Genes Associated with Smut in Sugarcane - Xiu-Peng Song; Dan-Dan Tian; Ming-Hui Chen; Zhen-Qiang Qin; Jin-Ju Wei; Chun-Yan Wei; Xiao-Qiu Zhang; De-Wei Li; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Boron Affects the Development of the Kidney Through Modulation of Apoptosis, Antioxidant Capacity, and Nrf2 Pathway in the African Ostrich Chicks - Haseeb Khaliq; Wang Jing; Xiao Ke; Yang Ke-Li; Sun Peng-peng; Lei Cui; Qiu Wei-wei; Lei Zhixin; Liu Hua-Zhen; Song Hui; Zhong Ju-Ming; Peng Ke-Mei (Biological Trace Element Research, 2018)

Rockburst occurrences and microseismicity in a longwall panel experiencing frequent rockbursts - Zhen-lei Li; Xue-qiu He; Lin-ming Dou; Gui-feng Wang (Geosciences Journal, 2018)

Permo–Triassic granitoids of the Xing’an–Mongolia segment of the Central Asian Orogenic Belt, Northeast China: age, composition, and tectonic implications - Qiu-Ming Pei; Shou-Ting Zhang; Ken-ichiro Hayashi; Hua-Wen Cao; Dong Li; Li Tang; Xin-Kai Hu; Hao-Xing Li; Da-Ren Fang (International Geology Review, 2018)

Wideband dipole logging based on segment linear frequency modulation excitation - Xue-Shen Cao; Hao Chen; Ping Li; Hong-Bin He; Yin-Qiu Zhou; Xiu-Ming Wang (Applied Geophysics, 2018)

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

Viral metagenomics of six bat species in close contact with humans in southern China - Xue-yan Zheng; Min Qiu; Wei-jie Guan; Jin-ming Li; Shao-wei Chen; Ming-ji Cheng; Shu-ting Huo; Zhong Chen; Yi Wu; Li-na Jiang; Qing Chen (Archives of Virology, 2018)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

Secretory expression of a novel human spermatozoa antigen in E. coli and its application to a protein chip - Ming-zhu Wang; Zhuo-lin Qiu; Xiang-Sheng Cai; Jing-jing Li; Miao-qin She; Yuan-feng Xu; Ying-song Wu (Biotechnology Letters, 2017)

Modulatory role of L-carnitine against microcystin-LR-induced immunotoxicity and oxidative stress in common carp - Xiu-Mei Chen; Gui-Liang Guo; Li Sun; Qiu-Shi Yang; Gui-Qin Wang; Dong-Ming Zhang (Fish Physiology and Biochemistry, 2017)

The Roles of Auxin in Regulating “Shoot Branching” of Cremastra appendiculata - Xiang Lv; Ming-Sheng Zhang; Yan-Qiu Wu; Xiao-Feng Gao; Xiao-Lan Li; Wang-Zhong Wang (Journal of Plant Growth Regulation, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

The Research on the Relationship of RAGE, LRP-1, and Aβ Accumulation in the Hippocampus, Prefrontal Lobe, and Amygdala of STZ-Induced Diabetic Rats - Lou-Yan Ma; Yu-Lang Fei; Xiao-Ye Wang; Song-Di Wu; Jun-Hui Du; Mei Zhu; Long Jin; Ming Li; Hai-Long Li; Jia-Jia Zhai; Lu-Peng Ji; Ran-Ran Ma; et al. (Journal of Molecular Neuroscience, 2017)

Serum Resistin Levels May Contribute to an Increased Risk of Acute Cerebral Infarction - Xiao-Liu Dong; Shi-Jun Xu; Li Zhang; Xiu-Qing Zhang; Ting Liu; Qiu-Yan Gao; Qing-Qiang Qian; Bao-Liang Sun; Ming-Feng Yang (Molecular Neurobiology, 2017)

Association Between Tumor Necrosis Factor-α and Diabetic Peripheral Neuropathy in Patients with Type 2 Diabetes: a Meta-Analysis - Ze-Peng Mu; Yan-Gang Wang; Cheng-Qian Li; Wen-Shan Lv; Bin Wang; Zhao-Hai Jing; Xue-Jia Song; Yu Lun; Ming-Yue Qiu; Xiao-Long Ma (Molecular Neurobiology, 2017)

Deriving characterization factors on freshwater ecotoxicity of graphene oxide nanomaterial for life cycle impact assessment - Yelin Deng; Jianyang Li; Ming Qiu; Fan Yang; Jingyi Zhang; Chris Yuan (The International Journal of Life Cycle Assessment, 2017)

U–Pb dating of zircon and cassiterite from the Early Cretaceous Jiaojiguan iron-tin polymetallic deposit, implications for magmatism and metallogeny of the Tengchong area, western Yunnan, China - Hua-Wen Cao; Yun-Hui Zhang; Qiu-Ming Pei; Rong-Qing Zhang; Li Tang; Bin Lin; Guo-Jun Cai (International Geology Review, 2017)

Truncated type IV pilin PilA108 activates the intramembrane protease AlgW to cleave MucA and PilA108 itself in vitro - Ronghui Li; Ryan T. Withers; Jingcheng Dai; Jing Ruan; Wei Li; Yujun Dai; Weixing An; Dianzhen Yu; Hehong Wei; Ming Xia; Chunyuan Tian; Hongwei D. Yu; et al. (Archives of Microbiology, 2016)

NF-κB Blockade in Hypothalamic Paraventricular Nucleus Inhibits High-Salt-Induced Hypertension Through NLRP3 and Caspase-1 - Jie Qi; Xiao-Jing Yu; Xiao-Lian Shi; Hong-Li Gao; Qiu-Yue Yi; Hong Tan; Xiao-Yan Fan; Yan Zhang; Xin-Ai Song; Wei Cui; Jin-Jun Liu; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Targeting Interleukin-1 beta to Suppress Sympathoexcitation in Hypothalamic Paraventricular Nucleus in Dahl Salt-Sensitive Hypertensive Rats - Jie Qi; Xiu-Fang Zhao; Xiao-Jing Yu; Qiu-Yue Yi; Xiao-Lian Shi; Hong Tan; Xiao-Yan Fan; Hong-Li Gao; Li-Ying Yue; Zhi-Peng Feng; Yu-Ming Kang (Cardiovascular Toxicology, 2016)

Paraventricular Nucleus Infusion of Epigallocatechin-3-O-Gallate Improves Renovascular Hypertension - Qiu-Yue Yi; Jie Qi; Xiao-Jing Yu; Hong-Bao Li; Yan Zhang; Qing Su; Tao Shi; Dong-Mei Zhang; Jing Guo; Zhi-Peng Feng; Mo-Lin Wang; Guo-Qing Zhu; et al. (Cardiovascular Toxicology, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Paenibacillus wenxiniae sp. nov., a nifH gene -harbouring endophytic bacterium isolated from maize - Jun-lian Gao; Fan-yang Lv; Xu-ming Wang; Tian-lei Qiu; Mei Yuan; Ji-wei Li; Yi Zhou; Jian-guang Sun (Antonie van Leeuwenhoek, 2015)

Prolonged overexpression of Wnt10b induces epidermal keratinocyte transformation through activating EGF pathway - Mingxing Lei; Xiangdong Lai; Xiufeng Bai; Weiming Qiu; Tian Yang; Xiaoling Liao; Cheng-Ming Chuong; Li Yang; Xiaohua Lian; Julia Li Zhong (Histochemistry and Cell Biology, 2015)

Mitochondria-Targeted Peptide Reverses Mitochondrial Dysfunction and Cognitive Deficits in Sepsis-Associated Encephalopathy - Jing Wu; Mingqiang Zhang; Shuangying Hao; Ming Jia; Muhuo Ji; Lili Qiu; Xiaoyan Sun; Jianjun Yang; Kuanyu Li (Molecular Neurobiology, 2015)

Impacts of the Wenchuan earthquake on tree mortality and biomass carbon stock - Shuai Qiu; Ming Xu; Yunpu Zheng; Renqiang Li; Michelle Hang Gi Wong; Liyun Zhang; Lixiang Liu; Changhong Lai; Wen Zhang (Natural Hazards, 2015)

Molecular and serological evidence for Seoul virus in rats (Rattus norvegicus) in Zhangmu, Tibet, China - Tingsong Hu; Quanshui Fan; Xiaobing Hu; Bo Deng; Gang Chen; Liangqi Gu; Ming Li; Ying Zheng; Guihong Yuan; Wei Qiu; Xiaomei Jiang; Fuqiang Zhang (Archives of Virology, 2015)

Effects of intermediate metabolite carboxylic acids of TCA cycle on Microcystis with overproduction of phycocyanin - Shijie Bai; Jingcheng Dai; Ming Xia; Jing Ruan; Hehong Wei; Dianzhen Yu; Ronghui Li; Hongmei Jing; Chunyuan Tian; Lirong Song; Dongru Qiu (Environmental Science and Pollution Research, 2015)

Characterization of monoclonal antibodies against duck Tembusu virus E protein: an antigen-capture ELISA for the detection of Tembusu virus infection - Xiaofei Bai; Wulin Shaozhou; Qingshan Zhang; Chenxi Li; Na Qiu; Runzhe Meng; Ming Liu; Yun Zhang (Archives of Virology, 2015)

Variovorax guangxiensis sp. nov., an aerobic, 1-aminocyclopropane-1-carboxylate deaminase producing bacterium isolated from banana rhizosphere - Jun-lian Gao; Mei Yuan; Xu-ming Wang; Tian-lei Qiu; Ji-wei Li; Hong-can Liu; Xiu-ai Li; Jian Chen; Jian-guang Sun (Antonie van Leeuwenhoek, 2015)

Downregulation of Neuregulin 1-ErbB4 Signaling in Parvalbumin Interneurons in the Rat Brain May Contribute to the Antidepressant Properties of Ketamine - Nan Wang; Guang-Fen Zhang; Xiao-Yu Liu; He-Liang Sun; Xing-Ming Wang; Li-Li Qiu; Chun Yang; Jian-Jun Yang (Journal of Molecular Neuroscience, 2014)

Breast Cancer Resistance Protein-Mediated Efflux of Luteolin Glucuronides in HeLa Cells Overexpressing UDP-Glucuronosyltransferase 1A9 - Lan Tang; Ye Li; Wei-Ying Chen; Shan Zeng; Ling-Na Dong; Xiao-Juan Peng; Wen Jiang; Ming Hu; Zhong-Qiu Liu (Pharmaceutical Research, 2014)

CRP Gene polymorphism contributes genetic susceptibility to dyslipidemia in Han Chinese population - Wenbin Wei; Song Yang; Yingru Qiu; Hairu Wang; Xianghai Zhao; Yanping Zhao; Yun Li; Ming Wu; Yanchun Chen; Wen Wang; Xiaoming Shi; Sijun Liu; et al. (Molecular Biology Reports, 2014)

Interaction Between AT1 Receptor and NF-κB in Hypothalamic Paraventricular Nucleus Contributes to Oxidative Stress and Sympathoexcitation by Modulating Neurotransmitters in Heart Failure - Xiao-Jing Yu; Yu-Ping Suo; Jie Qi; Qing Yang; Hui-Hua Li; Dong-Mei Zhang; Qiu-Yue Yi; Jian Zhang; Guo-Qing Zhu; Zhiming Zhu; Yu-Ming Kang (Cardiovascular Toxicology, 2013)

Molecular characterization of a duck Tembusu virus from China - XiaoFei Bai; Rang Lv; ChunGuo Liu; Na Qiu; Yilong He; XiuChen Yin; XiaoJun Li; Ming Liu; Yun Zhang (Virus Genes, 2013)

Characterization of novel polymorphic microsatellite markers from the cDNA library of Japanese scallop Mizuhopecten yessoensis and cross-species amplification in bay scallop Argopecten irradians - XIANG YING MENG; XIU LI WANG; XIAO LI GUO; MENG CHEN; YING MING ZHANG; HONG YUE WANG; YA QING CHANG; XUE MEI QIU (Journal of Genetics, 2013)

Using proteomic analysis to find the proteins involved in resistance against Sclerotinia sclerotiorum in adult Brassica napus - Li Wen; Tai-Long Tan; Jia-Bin Shu; Ying Chen; Ying Liu; Zhong-Fang Yang; Qiu-Ping Zhang; Ming-Zhi Yin; Jun Tao; Chun-Yun Guan (European Journal of Plant Pathology, 2013)

Progressive modelling of the gravity-induced landslide using the local dynamic strength reduction method - Guo-qing Chen; Run-qiu Huang; Qiang Xu; Tian-bin Li; Ming-lei Zhu (Journal of Mountain Science, 2013)
The failure of slope is a progressive process, and the whole sliding surface is caused by the gradual softening of soil strength of the potential sliding surface. From this viewpoint, a local dynamic strength reduction method is proposed to capture the progressive failure of slope. This method can calculate the warning deformation of landslide in this study. Only strength parameters of the yielded zone of landslide will be reduced by using the method. Through continuous local reduction of the strength parameters of the yielded zone, the potential sliding surface developed gradually and evolved to breakthrough finally. The result shows that the proposed method can simulate the progressive failure of slope truly. The yielded zone and deformation of landslide obtained by the method are smaller than those of overall strength reduction method. The warning deformation of landslide can be obtained by using the local dynamic strength reduction method which is based on the softening characteristics of the sliding surface.

Proteome Analysis of the Two-Component SalK/SalR System in Epidemic Streptococcus suis Serotype 2 - Xiaodong Shen; Qiu Zhong; Yan Zhao; Supeng Yin; Tian Chen; Fuquan Hu; Ming Li (Current Microbiology, 2013)

Identification of Major QTL for Waterlogging Tolerance Using Genome-Wide Association and Linkage Mapping of Maize Seedlings - Xiaobo Zhang; Bin Tang; Feng Yu; Liu Li; Ming Wang; Yadong Xue; Zuxin Zhang; Jianbing Yan; Bing Yue; Yonglian Zheng; Fazhan Qiu (Plant Molecular Biology Reporter, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Association of 10q23 with colorectal cancer in a Chinese population - Fen-Xia Li; Xue-Xi Yang; Xuan-Qiu He; Ni-Ya Hu; Ying-Song Wu; Ming Li (Molecular Biology Reports, 2012)

Molecular cloning and expression of gene encoding aromatic amino acid decarboxylase in ‘Vidal blanc’ grape berries - Qiu-Hong Pan; Fang Chen; Bao-Qing Zhu; Li-Yan Ma; Li Li; Jing-Ming Li (Molecular Biology Reports, 2012)

Changes of Brain Structure and Function in ADHD Children - Ming-guo Qiu; Zhang Ye; Qi-yu Li; Guang-jiu Liu; Bing Xie; Jian Wang (Brain Topography, 2011)

Polycyclic aromatic hydrocarbons in surface sediments of the Jialu River - Jie Fu; Sheng Sheng; Teng Wen; Zhi-Ming Zhang; Qing Wang; Qiu-Xiang Hu; Qing-Shan Li; Shu-Qing An; Hai-Liang Zhu (Ecotoxicology, 2011)

Characteristics of the lower layer of sandstorms in the Minqin desert-oasis zone - Ming Zhao; KeJie Zhan; ZiHui Yang; ErTian Fang; GuoYu Qiu; QiangQiang Wang; YinChang Zhang; ShuJiang Guo; AiDe Li; JingChun Zhang (Science China Earth Sciences, 2011)

Fungistatic Intensity of Agricultural Soil Against Fungal Agents and Phylogenetic Analysis on the Actinobacteria Involved - Li Zhi Fang; Xu Chuan Kun; Zou Chang Song; Xi Jia Qin; He Yue Qiu; Duan Chang Qun; Mo Ming He (Current Microbiology, 2011)

RA induces the neural-like cells generated from epigenetic modified NIH/3T3 cells - Xi-Mei Zhang; Qiu-Ming Li; Dong-Ju Su; Ning Wang; Zhi-Yan Shan; Lian-Hong Jin; Lei Lei (Molecular Biology Reports, 2010)

An improved process for cell disruption and astaxanthin extraction from Phaffia rhodozyma - An-Feng Xiao; Hui Ni; Hui-Nong Cai; Li-Jun Li; Wen-Jin Su; Qiu-Ming Yang (World Journal of Microbiology and Biotechnology, 2009)

Development and application of SCAR markers for sex identification in the dioecious species Ginkgo biloba L. - Liqin Liao; Jun Liu; Yanxia Dai; Qian Li; Ming Xie; Qijiong Chen; Huaqun Yin; Guanzhou Qiu; Xueduan Liu (Euphytica, 2009)

Molecular cloning, characterization and mRNA expression of peroxiredoxin in Zhikong scallop Chlamys farreri - Ming Cong; Duojiao Ni; Linsheng Song; Lingling Wang; Jianmin Zhao; Limei Qiu; Ling Li (Molecular Biology Reports, 2009)

ATG16L1 T300A polymorphism and Crohn’s disease susceptibility: evidence from 13,022 cases and 17,532 controls - Hai-Feng Zhang; Li-Xin Qiu; Yu Chen; Wa-Li Zhu; Chen Mao; Li-Guang Zhu; Ming-Hua Zheng; Yan Wang; Lei Lei; Jian Shi (Human Genetics, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

FAS −1,377 G/A polymorphism is associated with cancer susceptibility: evidence from 10,564 cases and 12,075 controls - Li-Xin Qiu; Jian Shi; Hui Yuan; Xin Jiang; Kai Xue; Hai-Feng Pan; Jin Li; Ming-Hua Zheng (Human Genetics, 2009)

Arabidopsis microtubule-associated protein AtMAP65-2 acts as a microtubule stabilizer - Hua Li; Xian Zeng; Zi-Qiang Liu; Qiu-Tao Meng; Ming Yuan; Tong-Lin Mao (Plant Molecular Biology, 2009)

Identification of QTLs for the resistance to rice stripe virus in the indica rice variety Dular - Shu-Jun Wu; Huan Zhong; Yong Zhou; Hui Zuo; Li-Hui Zhou; Jin-Yan Zhu; Cao-Qiu Ji; Shi-Liang Gu; Ming-Hong Gu; Guo-Hua Liang (Euphytica, 2009)

Mutation characteristics of the PAH gene in four nationality groups in Xinjiang of China - Wu-Zhong Yu; Dong-Hui Qiu; Fang Song; Li Liu; Shao-Ming Liu; Yu-Wei Jin; Yan-Ling Zhang; Hong-Yun Zou; Jiang He; Quan Lei; Xing-Wen Liu (Journal of Genetics, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

AFLP and ISSR analysis reveals high genetic variation and inter-population differentiation in fragmented populations of the endangered Litsea szemaois (Lauraceae) from Southwest China - Xiu-qin Ci; Jun-qiu Chen; Qiao-ming Li; Jie Li (Plant Systematics and Evolution, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Evoked membrane potential change in rat optic nerve fiber: Computer simulation - Vincent Cazenave-Loustalet; Qing-Li Qiao; Li-Ming Li; Qiu-Shi Ren (Neuroscience Bulletin, 2007)

Genetic Analysis of RET, EDNRB, and EDN3 Genes and Three SNPs in MCS + 9.7 in Chinese Patients with Isolated Hirschsprung Disease - Xian-Ning Zhang; Miao-Ni Zhou; Yun-Qing Qiu; Shi-Ping Ding; Ming Qi; Ji-Cheng Li (Biochemical Genetics, 2007)

Seasonal Variation of Virioplankton in a Eutrophic Shallow Lake - Yan-Ming Liu; Qi-Ya Zhang; Xiu-Ping Yuan; Zheng-Qiu Li; Jian-Fang Gui (Hydrobiologia, 2006)

A genetic diversity comparison between captive individuals and wild individuals of Elliot’s Pheasant (Syrmaticus ellioti) using mitochondrial DNA - Ping-ping Jiang; Qiu-lei Lang; Sheng-guo Fang; Ping Ding; Li-ming Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Plant Regeneration from Hypocotyl Protoplasts of Red Cabbage (Brassica Oleracea) by Using Nurse Cultures - Li-Ping Chen; Ming-Fang Zhang; Qiu-Bing Xiao; Jian-Guo Wu; Yutaka Hirata (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Aluminum content of tea leaves and factors affecting the uptake of aluminum from soil into tea leaves - Zhong-lei Xie; De-ming Dong; Guo-zhang Bao; Sheng-tian Wang; Yao-guo Du; Li-min Qiu (Chinese Geographical Science, 2001)